2001
DOI: 10.1002/nur.1014
|View full text |Cite
|
Sign up to set email alerts
|

Resourcefulness and health practices of diabetic women

Abstract: More than one fourth of the millions of Americans with Type 2 diabetes experience depression, of which two thirds are women. Unless the individual is resourceful, coexisting diabetes and depression adversely affect one' health practices. The effects of diabetic and depressive symptoms on health practices and the mediating and moderating role of learned resourcefulness in this relationship were examined in 90 women with Type 2 diabetes. Regression analyses showed direct negative effects of diabetic and depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 26 publications
1
28
0
1
Order By: Relevance
“…The score expected in the general population is +25 with a standard deviation of 20. Reliability and validity have been well established and reported internal consistency estimates were from .78 to .95 (Rosenbaum, 1990;Zauszniewski & Chung, 2001). The SCS was previously translated in Chinese to measure self-control in adolescents in Taiwan (Huang, Sousa, Tu, & Hwang, 2005).…”
Section: Learned Resourcefulnessmentioning
confidence: 98%
See 1 more Smart Citation
“…The score expected in the general population is +25 with a standard deviation of 20. Reliability and validity have been well established and reported internal consistency estimates were from .78 to .95 (Rosenbaum, 1990;Zauszniewski & Chung, 2001). The SCS was previously translated in Chinese to measure self-control in adolescents in Taiwan (Huang, Sousa, Tu, & Hwang, 2005).…”
Section: Learned Resourcefulnessmentioning
confidence: 98%
“…White, Tata, and Burns (1996) found that diabetic patients with high resourcefulness levels reported fewer hypoglycemic episodes. Learned resourcefulness was a partial mediating factor between depressive symptoms and health practices of individuals with diabetes (Zauszniewski & Chung, 2001). Individuals with diabetes who had greater learned resourcefulness and better glycemic control also had fewer depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The key component in his model is learned resourcefulness -the basic self-regulatory skills needed to handle everyday life challenges. Individuals possessing a large general repertoire of learned resourcefulness skills make use of positive self-instructions, delay gratification, apply problem-solving methods and employ other self-control strategies when dealing with negative emotions (Rosenbaum & Cohen, 1999), breaking bad habits (Kennett, Morris, & Bangs, 2006), adhering to medical regimens (Zauszniewski & Chung, 2001), or overcoming other adversities they encounter (Edwards & Riordan, 1994;McWhirter, 1997). Evidence shows that these skills begin to develop in early childhood, through interaction and modelling from others (Preechawong et al, 2007;Turkel & Tezer, 2008;Zauszniewski, Chung, Chang, & Krafcik, 2002), and become stable by early adulthood (Rosenbaum, 1990).…”
Section: Importance Of General Learned Resourcefulness Skillsmentioning
confidence: 99%
“…Mothers with challenges due to bipolar illness can draw on resourcefulness to manage variations in their disorder and mothering (Zauszniewski, 2006;Zauszniewski & Musil, 2012). Overall resourcefulness (the total of self-help and help-seeking) has been found to have a strong direct effect on health practices (Zauszniewski & Chung, 2001). We included the direct effect of resourcefulness because we don't expect that self-help and help-seeking will completely account for the effects of resourcefulness on mothering quality.…”
Section: Resourcefulnessmentioning
confidence: 99%